Strategic Management of Educational Operational Grants: Enhancing Quality and Excellence in Learning Outcomes - Novaliza, Ferti; Widayatsih, Tri; Rosani, Meilia (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
The strategic management of Educational Operational Grants (Indonesia: Bantuan Operasional Penyelenggaraan Pendidikan - Pusat Kegiatan Belajar Mengajar BOP-PKBM) at PKBM Melati in Ogan Ilir plays a vital role in enhancing the quality of non-formal education. This study aimed to explore the effectiveness of strategic management practices in optimizing the use of BOP funds to improve educational outcomes. Using a qualitative research approach, data were collected through interviews, observations, and documentation involving key stakeholders such as the school principal, treasurer, tutors, and local education authorities. The findings reveal that the management at PKBM Melati prioritizes efficient allocation of funds towards critical areas like teacher training, curriculum development, and facility maintenance. Transparency is maintained through clear reporting mechanisms, ensuring all stakeholders are informed about fund utilization. Additionally, community involvement in the management and oversight of BOP funds fosters a shared responsibility for educational quality. Regular evaluations are conducted to assess the effectiveness of fund usage, with adjustments made as necessary to maximize impact. The study concludes that strategic planning, stakeholder collaboration, continuous evaluation, and rigorous oversight are essential components for achieving sustainable improvements in educational quality at PKBM Melati. The research contributes valuable insights into the strategic management of educational grants in non-formal settings, emphasizing the need for comprehensive planning and accountability to meet the educational needs of underserved communities.